Malaysian early career researchers on the ethics of scholarly publishing - Abrizah, A.; Ahmad Kharman Shah, Nordiana; Nicholas, David (Malaysian Journal of Library and Information Science, 2019)
Publication ethics are rarely taught. This paper presents research into the knowledge of scholarly publishing ethics among Malaysian early-career researchers (ECRs). This research comes from year two of a projected three-year-long study of ECRs from seven countries (China, France, Malaysia, Poland, Spain, the UK, and the US), for which semi-structured indepth interviews were conducted with study participants. For the findings reported in this paper, 12 ECRs from science and social science disciplines at five Malaysian researchintensive universities were interviewed during the period from February to June 2017. The interview record was compared with the previous year’s (2016) record to identify changes in interviewees’ responses to a set of questions on their knowledge of ethics in scholarly communication. In addition, contextual data were obtained from the CVs of the ECRs. Our findings indicate that the attitudes and behaviours of Malaysian ECRs in relation to scholarly communication ethics have changed in the passage of one year. We observed noteworthy changes in ECRs’ knowledge of unethical behaviours. As compared with data from 2016, the ECRs are more verbose in their responses on what is generally regarded as ethical and unethical in research and/or publishing practices. Authorship policies, the academic evaluation system, and the scrutiny which will keep the lid on any unethical behaviours are the most important factors bringing about the changes we observed. This paper suggests that ECRs’ manifestation of publishing ethics is gauged through their publishing practices.